2010
DOI: 10.1159/000276303
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety and Efficacy of a Novel Thermoreversible Polyhexanide-Preserved Wound Covering Gel

Abstract: Background: An ideal topical formulation for wound therapy does not exist. The aim of this study was to develop a novel improved therapeutic option for the treatment of acute and chronic wounds. Methods: A transparent wound gel which is in a liquid state below and in a gel state at or above room temperature was developed. Forty-four patients were included in this open randomized controlled single-center study. Flammazine™ served as control in the treatment of skin graft donor sites. Wounds were assessed for ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 34 publications
3
13
0
Order By: Relevance
“…These growth factors are known to be the key factors for stimulating angiogenesis . Our findings confirm the low toxicity and excellent tissue tolerance of polyhexanide . The advantage over the control group is possibly also caused by an improvement in the tissue perfusion and therefore increased metabolism .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…These growth factors are known to be the key factors for stimulating angiogenesis . Our findings confirm the low toxicity and excellent tissue tolerance of polyhexanide . The advantage over the control group is possibly also caused by an improvement in the tissue perfusion and therefore increased metabolism .…”
Section: Discussionsupporting
confidence: 80%
“…Its transparency allows a direct assessment of the wound. Our previous studies as well as the data obtained from other groups showed excellent results concerning toxicity and wound healing in experimental and clinical setups .…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…The treatment of burns includes cooling, antiphlogistics, and painkillers, local disinfection, and moist dressings [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The open randomized controlled single-center study was carried out on 44 patients in 2 parallel groups (Traumasept®wound covering gel vs. Flammazine®). The transparency of the thermosensitive gel formulation and absence of staining allowed for good wound assessment, without the need for painful cleaning, and the change from the fluid to the gel state enabled easy handling and filling the wound cavities (Goertz et al, 2010). One of the most important parameters of the injured tissue pathology is to stop the bleeding and to protect the area with a protective support material in the first step.…”
Section: Wwwintechopencommentioning
confidence: 99%